Risk factors for diseases of the cardiovascular system among Catholics living in areas of southern Poland - Majda, Anna; Zalewska-Puchała, Joanna; Kamińska, Alicja; Bodys-Cupak, Iwona; Suder, Marcin (Medical Studies/Studia Medyczne, 2017)
Introduction : Cardiovascular diseases (CVD) are the most frequent cause of mortality of Polish residents. In Poland, there are few publications regarding research on the influence of people’s religiosity on their health. Aim of the research : To determine some factors of cardiovascular risk and the risk of cardiovascular events among Catholics. Material and methods: This cross-sectional study was conducted among 134 randomly selected Catholics and based on the results of: questionnaire survey, anthropometric measurements, physical examination, the SCORE scale, laboratory tests (CRP, homocysteine. glucose, total cholesterol, HDL, and triglycerides) and assessing the risk of cardiovascular events based on the SCORE scale. Statistical analysis was based on the χ 2 test. Founded significance level was 0.05. Results: More than half of the respondents were diagnosed delevated homocysteine level and gluteal-femoral obesity. A little more than half of those surveyed had elevated total cholesterol levels and increased blood pressure, a little more than one-quarter of the respondents had raised triglyceride levels, and one-tenth had heightened glucose and C-reactive protein levels. The higher the age of the respondents, the more often the results of their biochemical exceed standards. Over half of those examined were diagnosed with overweight or obesity. Among examined gynoid obesity prevailed over android obesity. The risk assessment of CVD Catholics revealed that among the modifiable factors, biochemical levels of homocysteine proved to be the most important new risk factor, but among the classic factors it was blood pressure value. More than half of the respondents had moderate risk of cardiovascular events in the study group. Conclusions : Nurses should promote pro-health attitudes, and should encourage the elimination of risk factors and biochemical testing and measurement among Catholics, who are a religious group at higher risk of cardiovascular disease.